Transformasi dan Kajian Etnopedagogi Naskah Wawacan Sulanjana - Dingding Haerudin; Dedi Koswara (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
This paper examines the results of the transformation of the Ancient Sundanese script entitled